Breathing pattern and pulmonary gas exchange in elderly patients with and without left ventricular dysfunction—modification with exercise-based cardiac rehabilitation and prognostic value - Eser, Prisca; Marcin, Thimo; Prescott, Eva; Prins, Leonie F.; Kolkman, Evelien; Bruins, Wendy; van der Velde, Astrid E.; Gil, Carlos Peña; Iliou, Marie-Christine; Ardissino, Diego; Zeymer, Uwe; Meindersma, Esther P.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Inefficient ventilation is an established prognostic marker in patients with heart failure. It is not known whether inefficient ventilation is also linked to poor prognosis in patients with left ventricular dysfunction (LVD) but without overt heart failure.Is To investigate whether inefficient ventilation in elderly patients with LVD is more common than in patients without LVD, whether it improve with exercise-based cardiac rehabilitation (exCR), and whetheris it is associated with major adverse cardiovascular events (MACE).?In this large multicentre observational longitudinal study, patients aged ≥65 years with acute or chronic coronary syndromes (ACS, CCS) without cardiac surgery who participated in a study on effectiveness of exercise-based cardiac rehabilitation (exCR) in seven European countries were included. Cardiopulmonary exercise testing (CPET) was performed before, at termination of exCR and at 12 months follow-up. Ventilation (VE), breathing frequency (BF), tidal volume (VT) and end-expiratory carbon dioxide pressure (PETCO2) were measured at rest, at first ventilatory threshold and peak exercise. Ventilatory parameters were compared between patients with and without LVD (based on cardioechography) and related to MACE at 12 month-follow up.In 818 patients, age was 72.5±5.4 years, 21.9% were women, 79.8% had ACS, and 151 (18%) had LVD. Compared to noLVD, in LVD resting VE was increased 8%, resting BF 6%, peak VE, peak VT, and peak PETCO2 reduced by 6%, 8%, and 5%, respectively, and VE/VVCO2 slope increased by 11%. From before to after exCR, resting VE decreased and peak PETCO2 increased significantly more in patients with compared to without LVD. In LVD, higher resting BF, higher nadir VE/VCO2, and lower peak PETCO2 at baseline were associated with MACESimilarly to patients with HF, in elderly patients with ischemic LVD, inefficient resting and exercise ventilation wais associated with worse outcome, and ExCR alleviateds abnormal breathing patterns and gas exchange parameters.